The Impact of Internal Control on Project Management in Construction Site Among Small and Medium Enterprises in Iraq - Abdulhadi, Ali Raqee; Ariffin, Mohd Khairol Bin; Leman, Zulkiflle B; Ahmad, Siti Azfanizam; Al-Zubaidi, Razi; Abdulsamad, Akram (Advances in Social Sciences Research Journal, 2023)
The present study investigates the relationship between internal control and project management among Iraq construction SMEs. The current research is focused on internal control as multi-dimensional by using its four main components, which are control environment, control activities, self-assessment, and information & communication, while project management was taken as unidimensional. Data were gathered from the employees who are working in construction SMEs in Iraq, either consultants, developers, or contractors. 251 questionnaires were received and analyzed by using SPSS and smart PLS-SEM to measure the research model fit and examine the hypothesis, whether accepted or not within the study context. The model measurement and structural equation model test indicated that all four main hypotheses were accepted, which means that internal control has a positive impact on the four main components of project management in SMEs in the construction sectors in Iraq. Also, the theoretical and managerial implications of this research were then discussed at the end of this article.